COVID-19: Growing Health Disparity Gaps and an Opportunity for Health Behavior Discovery? (Mary Ann Liebert, 2020)
Recently, racial and ethnic disparities within the current coronavirus disease-2019 (COVID-19) pandemic at the state level have received attention and notably highlight the ongoing issues surrounding health disparities within the United States. Among the discussions around health disparities lies a discussion on the role of psychosocial stress during this pandemic, especially with broadly applied social distancing and isolation recommendations. In nonpandemic times, psychosocial stressors have a significant association with physiological responses and behavioral responses. Within the current pandemic, increased attention on health-promoting behaviors, such as cooking and physical activity, has occurred. However, based on disparities from structural racism and socioeconomic effects on neighborhood environments, we may see a limiting value to the possible mitigating role of health behaviors within some disparate communities. We present in this perspective that there may be a role for behavioral interventions to mitigate psychosocial stressors and promote health behaviors. It may also be important to consider the use of multilevel behavioral interventions designed in the context of environmental and perceptual barriers during the COIVD-19 pandemic.